Binge eating in adults with mood disorders: Results from the International Mood Disorders Collaborative Project. Issue 5 (September 2016) - Woldeyohannes, Hanna O.; Soczynska, Joanna K.; Maruschak, Nadia A.; Syeda, Kahlood; Wium-Andersen, Ida K.; Lee, Yena; Cha, Danielle S.; Xiao, Holly X.; Gallaugher, Laura A.; Dale, Roman M.; Alsuwaidan, Mohammad T.; Mansur, Rodrigo B.; et al.
Summary: A post hoc analysis was conducted using data from participants ( N  = 631) with a DSM-IV-TR defined diagnosis of major depressive disorder (MDD) or bipolar disorder (BD) who were enrolled in the International Mood Disorders Collaborative Project (IMDCP) between January 2008 and July 2013. It was determined that 20.6% of adults with mood disorders as part of the IMDCP fulfilled criteria for binge eating behaviour (BE). A higher percentage of individuals with BD met criteria for BE when compared to MDD (25.4% vs. 16%; p  = 0.004) Univariate analyses indicated that individuals with a mood disorder (i.e., MDD or BD) and BE had greater scores on measures of anxiety severity ( p  = 0.013) and higher rates of lifetime and current substance dependence, lifetime alcohol abuse ( p  = 0.007, p  = 0.006, and p  = 0.015, respectively), Attention Deficit Hyperactivity Disorder (ADHD) ( p  = 0.018) and measures of neuroticism ( p  = 0.019). Individuals with a mood disorder and concurrent BE had lower scores on measures of conscientiousness ( p  = 0.019). Individuals meeting criteria for BE were also significantly more likely to be obese (i.e., BMI ≥ 30 kg/m 2 ) (50% vs. 25.5%; p  < 0.001). Binge eating is common amongst adults utilising tertiary care services principally for a mood disorder. The presence of BE identifies a subset of adults with mood disorders who have greater illness complexity as evidenced by course of illness variables and comorbidity. Screening for BE amongst individuals with mood disorders is warranted; parsing neurobiological substrates subserving non-homeostatic eating behaviour amongst individuals with mood disorders is a future research vista.